2009
DOI: 10.1258/td.2008.080248
|View full text |Cite
|
Sign up to set email alerts
|

Atypical bacterial pathogens in community-acquired pneumonia in children: a hospital-based study

Abstract: A total of 243 children aged one month to five years with World Health Organization defined severe community acquired pneumonia were studied for the presence of atypical bacterial pathogens: 24 were found positive for mycoplasma infection. There was no significant association with any of the clinical, laboratory and radiological variables in children with pneumonia by the atypical pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 8 publications
3
18
0
1
Order By: Relevance
“…species of these two genera are described as atypical pathogens for pneumonia [35], other studies have identified ''atypical pathogens'' as the predominant species in respiratory tract infections [15]. These findings are similar to previously published data for comparisons of traditional culture and culture-independent methods [6].…”
Section: Discussionsupporting
confidence: 85%
“…species of these two genera are described as atypical pathogens for pneumonia [35], other studies have identified ''atypical pathogens'' as the predominant species in respiratory tract infections [15]. These findings are similar to previously published data for comparisons of traditional culture and culture-independent methods [6].…”
Section: Discussionsupporting
confidence: 85%
“…Several genera of important possible pathogens were detected by the 454 platform but were absent from the list obtained by the clinical method. According to our knowledge and published articles, Mycoplasma, Haemophilus, and Moraxella are referred to as atypical pathogens of pneumonia [5,[26][27][28]. Compared with clinical reports, these potential pathogens were only found sporadically by our method in sputum samples.…”
Section: This Indicates That Althoughmentioning
confidence: 81%
“…The most common concern was unclear reporting of baseline study population characteristics. We had concerns about the spectrum of patients recruited and the validity of the reference standard in one study (Agarwal 2009) Summary of findings 2. Diagnostic value of clinical symptoms and signs -pooled results with 95% confidence intervals Somer 2006).…”
Section: Quality Concernsmentioning
confidence: 99%